The mechanism of lncRNA TALNEC2 regulating miR-19a-3p/JNK to alleviate cerebral ischemia injury in rats with acute cerebral infarction: lncRNA TALNEC2 regulating miR-19a-3p/JNK to alleviate cerebral ischemia injury in rats - Luan, Danping; Jiang, Chun (Cellular and Molecular Biology, 2022)
Ischemia-reperfusion (I-R) is renowned as a key approach in recovery related to cerebral infarction and further promotes succeeding infarction development. This study investigated the fundamental molecular function of the TALNEC2 in the pathogenesis of cerebral infarction to provide insights on the potential novel therapeutic agents in cerebral infarction. RT-qPCR measured expression of TALNEC2 and JNK in human neural cell line SH-SY5Y. Cell transfection upregulated or silenced the genes with MTT assay examining cell viability. RT-qPCR detected cell death in the apoptosis biomarker caspase-3, inflammation in the biomarkers C-reactive protein (CRP) and IL-6 and verified cell proliferation via the ki67 and PCNA markers. Luciferase assay was performed to see the luciferase activity and western blotting determined the protein expression of JNK in proliferation, inflammation. The results demonstrated that TALNEC2 was highly expressed after OGD/R treatment in nerve cells after cerebral infarction. In addition, TALNEC2 silencing prevented apoptosis and inflammation of nerve cells after cerebral infarction. TALNEC2 directly interacted with miR-19a-3p to regulate JNK protein expression. Lastly, miR-19a-3p inhibitor abolished the protective effect of si-TALNEC2 against OGD/R induced damage in vitro. In summary, this study has demonstrated that TALNEC2 is a positive moderator for pathogenesis of cerebral infarction. Furthermore, our conclusions provide further insights on the interplay among TALNEC2, miR-19a-3p and JNK in cerebral infarction. It has demonstrated herein that TALNEC2 positively modulates JNK post‐transcriptional expression through miR-19a-3p sponging in cerebral Infarction offering a novel therapy target for cerebral infarction.